Pathogen Profile of Patients with Sepsis in Internal Medicine, Dr. Hasan Sadikin General Hospital, Bandung 2013 - Afiq Syazwan Fauzi; Uun Sumardi; Nina Tristina (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Sepsis is a continuous disease which begins with systemic inflammatory response syndrome (SIRS), seen in association with a large number of clinical conditions. These include infectious insults that produce SIRS, such as pancreatitis, ischemia, multiple traumas and tissue injury, hemorrhagic shock, immunemediated organ injury, and the exogenous administration of such putative mediators of the inflammatory process as tumor necrosis factor and other cytokines. A frequent complication of SIRS is the development of organ system dysfunction, including such well-defined clinical conditions as acute lung injury, shock, renal failure, and multiple organ dysfunction syndrome (MODS). Hence, this study was conducted to identify the pathogen profile that often causes sepsis.Methods: A retrospective study was performed to 152 medical records of patients diagnosed as sepsis from Internal Medicine Department Dr. Hasan Sadikin General Hospital from January 2013 to December 2013. The variables observed from the medical records were age, sex, comorbidity, main infection, culture sample, type of gram bacteria, resistant bacteria, and antibiotic susceptibility test. After data collection was completed, the data were analyzed using computer. The data were presented in percentage.Results: Sepsis in male was higher than female. Highest comorbid was chronic kidney disease (CKD). The main infection was health care acquired pneumonia (HCAP). Highest pathogen that caused sepsis was Escherichia coli and highest multidrug-resistant organism (MDRO) was extended spectrum beta-lactamase(ESBL) Escherichia coli.Conclusions: The most common pathogen that causes sepsis is Escherichia coli. [AMJ.2016;3(2):200–5]DOI: 10.15850/amj.v3n2.785